Environmental Education Strategies for Supporting Sustainable Waste Management: a Systematic Literature Review - Intan Hayun Ningrum; Entoh Tohani; Sugito (Postgraduate, University of Mataram, 2025)
The study identifies and synthesizes strategies used in environmental education programs aimed at improving waste management behavior through a Systematic Literature Review (SLR) using the Scopus database. The analysis highlights three widely applied strategies: project-based learning, which engages students in recycling and conservation projects; experiential learning, which emphasizes real experiences for deeper understanding; and community-based training, which empowers communities to apply environmental knowledge in daily life. These strategies are often integrated with dialogic processes and digital media (e.g., blogs, animated videos, worksheets) to enhance environmental awareness and sustainable practices. The findings confirm that these approaches effectively increase understanding, awareness, and community participation in waste management. This study reinforces the importance of targeted environmental education in driving behavioral change and serves as a reference for designing sustainable environmental programs.